If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + -2(7z + -2) = 4(-6z + 2) + -4 Reorder the terms: -6 + -2(-2 + 7z) = 4(-6z + 2) + -4 -6 + (-2 * -2 + 7z * -2) = 4(-6z + 2) + -4 -6 + (4 + -14z) = 4(-6z + 2) + -4 Combine like terms: -6 + 4 = -2 -2 + -14z = 4(-6z + 2) + -4 Reorder the terms: -2 + -14z = 4(2 + -6z) + -4 -2 + -14z = (2 * 4 + -6z * 4) + -4 -2 + -14z = (8 + -24z) + -4 Reorder the terms: -2 + -14z = 8 + -4 + -24z Combine like terms: 8 + -4 = 4 -2 + -14z = 4 + -24z Solving -2 + -14z = 4 + -24z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '24z' to each side of the equation. -2 + -14z + 24z = 4 + -24z + 24z Combine like terms: -14z + 24z = 10z -2 + 10z = 4 + -24z + 24z Combine like terms: -24z + 24z = 0 -2 + 10z = 4 + 0 -2 + 10z = 4 Add '2' to each side of the equation. -2 + 2 + 10z = 4 + 2 Combine like terms: -2 + 2 = 0 0 + 10z = 4 + 2 10z = 4 + 2 Combine like terms: 4 + 2 = 6 10z = 6 Divide each side by '10'. z = 0.6 Simplifying z = 0.6
| 2-3f-5-5f=6 | | 2(0)-(9)= | | -8(1+7n)=-400 | | 3(8-z)-44=21z-4(5+6z) | | 2x-11=6x+9 | | 8.6+1.5x=17.7+x | | 26=4/u+2 | | 0.25x+4=0.12x+10 | | 9x^2+36=36x | | 3u+8=17 | | 2y+5/2-37/2=0 | | 6/p=5/11 | | 1-(3/(2x))=7/4 | | -6+5u=-16 | | 5+2n-2=7n+9-3n | | 3/p=7/9 | | -v+25=166 | | 36(2)= | | 114=155-v | | 3x+2x=-13 | | 166=-x+282 | | 0.06+0.03(100-x)=1.2 | | 7/3+4y=8y-1/15 | | 5[2x-7]=2 | | 5[2x-7]=2 | | 5.9+7.3x=11.5x | | 5(3x+4)=4(6x-4) | | 2(3b-4)=2(n+3) | | -x+169=281 | | 3/8=24c | | 4a-5+2a+9=21 | | 9-3x+12=15 |